1993
DOI: 10.1164/ajrccm/148.6_pt_1.1571
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragmatic Fatigue after Exercise in Healthy Human Subjects

Abstract: The purpose of this study was to determine whether diaphragmatic fatigue occurs after high-intensity constant-load whole-body exercise to volitional exhaustion. Ten sedentary subjects with a maximal oxygen uptake of 2.52 +/- 0.47 L/min were studied. Subjects exercised on a bicycle ergometer at 80% of their maximal working capacity until volitional exhaustion. Minute ventilation during the last minute of exercise was 89.9 +/- 13.6 L/min, which represented 50 +/- 6% of the subjects' 12-s maximal voluntary ventil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
82
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(90 citation statements)
references
References 28 publications
8
82
0
Order By: Relevance
“…In a recent study of 3 our laboratory, Renggli et al (Renggli et al, 2008) showed an increase in the ratio of oesophageal to transdiaphragmatic pressure generation during prolonged normocapnic hyperpnoea suggesting a partial takeover of diaphragmatic work by inspiratory rib cage muscles, similar to what was observed during exercise (Johnson et al, 1993;Mador et al, 1993).…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…In a recent study of 3 our laboratory, Renggli et al (Renggli et al, 2008) showed an increase in the ratio of oesophageal to transdiaphragmatic pressure generation during prolonged normocapnic hyperpnoea suggesting a partial takeover of diaphragmatic work by inspiratory rib cage muscles, similar to what was observed during exercise (Johnson et al, 1993;Mador et al, 1993).…”
Section: Introductionsupporting
confidence: 53%
“…Although volitional measures of fatigue may be confounded by the presence of central fatigue, the decrease in end-inspiratory V rc,p with no change in the other two compartments is considered an independent indicator of inspiratory rib cage muscle fatigue. Furthermore, the few studies assessing respiratory muscle fatigue after exercise with both measurement of oesophageal and gastric pressure during nerve stimulation and during voluntary respiratory manoeuvres show a decrease in twitch pressures with smaller decreases (or no significant change) in pressures during voluntary manoeuvres (Johnson et al, 1993;Mador et al, 1993;Taylor et al, 2006;Kabitz et al, 2008;Taylor and Romer 2008).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors9 laboratory has considerable experience with CMS and transcutaneous electrical stimulation in normal subjects and patients [6,12,[19][20][21][22]. CMS was utilised in the present study because this method is well tolerated and technically easier to perform than transcutaneous electrical stimulation.…”
Section: Critique Of Methodsmentioning
confidence: 99%
“…Normal subjects demonstrated evidence of diaphragmatic fatigue after voluntary hyperpnoea at a V9E of 60% MVV sustained for y8 min [21]. Furthermore, diaphragmatic fatigue was found in normal volunteers after endurance exercise in which subjects exercised for a mean of 8 min at a V9E that was 50% of their MVV [22]. JOHNSON et al [24] suggested that high-intensity exercise should be sustained for o10 min in order to produce significant diaphragmatic fatigue.…”
Section: Critique Of Methodsmentioning
confidence: 99%